Investigating How People and Culture Risk Perception Influences Risk Management in the South African Banking Sector - Monama, Lancelot; Ferreira-Schenk, Sune; Sgammini, Ruschelle; Mathlaku, Kago Amiel (International Journal of Economics and Financial Issues, 2025)
The purpose of this study is to investigate how bank workers’ perceptions and understandings of culture and people risk in the South African banking sector influenced operational and overall risk management during the COVID-19 epidemic. To do this, a questionnaire survey was created and distributed to staff at the main five South African banks: ABSA, FNB, Nedbank, Capitec Bank, and Standard Bank; 391 questions were analysed. The analysis methods used included basic statistical, correlation, and factor analysis. The findings revealed that during the pandemic, understanding cultural risk and people risk had a good effect on operational risk and general risk management in the banking sector. This suggests that since people risk and culture risk are better perceived and understood, risk management in banks during COVID-19 has improved overall. This research adds to the body of knowledge on risk by demonstrating how risk management is influenced by how both risk factors are seen and by emphasising the need to foster an organizational culture that produces “good people.” As a result, operational risk is decreased and bank risk management procedures are enhanced. One suggestion is that, in order to minimise unanticipated operational risk management quirks, banks’ employers should cultivate favorable organizational cultures.